On the existence and properties of periodic solutions of discrete difference equations - Pelyukh, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We establish conditions for the existence of periodic solutions for a broad class of nonlinear difference equations with discrete argument.